Design of an ecological network of conservation between La Amistad Biosphere Reserve and the protected areas of the Area of Conservation Osa, Costa Rica - Céspedes Agüero, Margarita V. (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006